Enthalpies of Solution of the Nucleic Acid Bases. 6. Guanine in Aqueous HCl and NaOH, and Guanine Hydrochlorides in Aqueous HCl - Kilday, Marthada V. (J Res Natl Bur Stand (1977), 1981)
The following values of the enthalphy of solution of well-characterized samples of guanine were obtained from measurements in an adiabatic solution calorimeter: [Table: see text] The following enthalpies of protonation were calculated for guanine: [Table: see text]